The chromosome-level genome assembly of goldstripe ponyfish (Karalla daura) reveals its similarity to Chinese sillago on contracted immune gene families - He, Wenping; Shi, Mijuan; Xia, Xiao-Qin; Zhang, Wanting; Yao, Weizhi; Gao, Tianxiang (Frontiers in Marine Science, 2022)
The goldstripe ponyfish is a small tropical economic fish in the Leiognathidae family. The genome of this fish was assembled as 24 chromosomes with a total length of 577.66 Mb and 54.81 Mb unanchored contigs using HiFi and Hi-C sequencing technologies. There are 256.7 Mb of repeat elements, which cover 40.59% of the genome, and 21,506 coding genes, which cover 47.68%. According to phylogenetic analysis, the goldstripe ponyfish is closely related to the Sillaginidae family’s Chinese sillago. The distance between goldstripe ponyfish and Chinese sillago in the hierarchical clustering of gene family contractions and expansions is also the shortest, indicating a similarity even greater than that between croakers of the same family (Sciaenidae). The goldstripe ponyfish and Chinese sillago share 25 identical contracted gene families, the majority of which are immune recognition receptors, such as innate immunity-related C-type lectin and butyrophilin families, as well as acquired immunity-related T-cell receptor region V and the surface glycoprotein CD4, implying that these two fishes’ immune systems may adopt similar evolutionary strategy at the genomic level. Additionally, the positively selected genes of the Chinese sillago and the goldstripe ponyfish were enriched in biological functions involved in the cell cycle, such as telomeres, which may account for the disparities in body size and lifespan between the two species.